For the orbital angular momentum, the raising and lowering operators are given by,
$$ L_+ = e^{i\phi} \bigg(\frac{\partial}{\partial\theta} + i\: cot\theta\frac{\partial}{\partial\phi}\bigg) $$ $$ L_- = -e^{-i\phi} \bigg(\frac{\partial}{\partial\theta} - i\: cot\theta\frac{\partial}{\partial\phi}\bigg) $$
With this I obtain $$ L_+^\dagger = - L_- $$ But with the actual definition in terms of $ L_x $ and $ L_y $ with $$ L_+ = L_x + i L_y $$ $$ L_- = L_x - i L_y $$ $$ L_+^\dagger = L_- $$
How do I reconcile between these two results ? Or is there any mistake I have committed ?
PS : My professor hinted saying it had something to do with compactness of angular momentum, but I didn't understand !! (My problem is not in obtaining the result of $L_+$ and $L_-$, but in reconciling these two facts).